2015
DOI: 10.1002/ece3.1572
|View full text |Cite
|
Sign up to set email alerts
|

Validation of daily increment formation in otoliths for Gymnocypris selincuoensis in the Tibetan Plateau, China

Abstract: Daily increment validation in fish otolith is fundamental to studies on fish otolith microstructure, age determination and life history traits, and thus is critical for species conservation and fishery management. However, it has never been done for Schizothoracine fish, which is the dominant component of fish fauna in the Tibetan Plateau. This study validated the daily increment formation of Gymnocypris selincuoensis, as a representative of Schizothoracine fish, by monitoring the growth of hatchery-reared lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 27 publications
(42 reference statements)
2
26
0
Order By: Relevance
“…Compared with populations inhabiting the lower‐altitude reaches, the higher altitude populations experienced lower water temperatures and shorter growing seasons. Such results are consistent with previous studies on other Schizothoracinae fish (Ding et al., ; Tao et al., ). Rearing experiments also found that temperature could enhance the growth of Schizothorax (Racoma) kozlovi as long as the temperature was below 32°C (He et al., ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Compared with populations inhabiting the lower‐altitude reaches, the higher altitude populations experienced lower water temperatures and shorter growing seasons. Such results are consistent with previous studies on other Schizothoracinae fish (Ding et al., ; Tao et al., ). Rearing experiments also found that temperature could enhance the growth of Schizothorax (Racoma) kozlovi as long as the temperature was below 32°C (He et al., ).…”
Section: Discussionsupporting
confidence: 94%
“…Schizothoracinae fish (Cyprinidae, Cypriniformes) are the predominant vertebrate group in aquatic ecosystems of the Tibetan Plateau and adjacent areas. Our previous study found that the Schizothoracinae fish can be powerful in the detection of environmental or climate changes (Tao et al, 2015). However, few studies related to growth variation have been done in this group (He et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Hence, age of wild C. molitorella can be estimated from the number of increments in lapilli. Daily increments in otoliths have been verified for other Cypriniformes (Green et al ., ; Yan et al ., ; Ding et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Increment counts also confirmed daily increments deposition in otolith of S. cephalus . These results are consistent with previous findings on larval and juvenile cyprinids (Morioka & Matsumoto, ; Ding et al ., ; Yan et al ., ).…”
Section: Discussionmentioning
confidence: 99%